Employment Effects of Welfare Reforms - Evidence from a Dynamic Structural Life-cycle Model. - Haan, P; Prowse, V; Uhlendorff, A (Department of Economics (University of Oxford), 2008)
In this paper we develop a dynamic structural life-cycle model of labor supply behavior which fully accounts for the eects of income tax and transfers on la- bor supply incentives. Additionally, the model recognizes the demand side driven rationing risk that might prevent individuals from realizing their optimal labor supply state, resulting in involuntary unemployment. We use this framework to study the employment eects of transforming a traditional welfare state, as is cur- rently in place in Germany, towards a more Anglo-American system in which a large proportion of transfers are paid to the working poor.